2013
DOI: 10.3233/jad-121945
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Pyroglutamate Amyloid-β is Present in Microglia and a Subfraction of Vessels in Patients with Alzheimer's Disease: Implications for Immunotherapy

Abstract: N-terminally truncated pyroglutamate amyloid-β (Aβ) starting at position 3 (AβpE3) represents a major fraction of Aβ peptides in Alzheimer's disease (AD). Recently, we have identified low molecular weight AβpE3 oligomers, which can be detected by 9D5, a novel mouse monoclonal antibody. In the present study, we analyzed the immunohistochemical staining profile in the brain of patients with AD and in the APP/PS1KI mouse model, as well as in aged rhesus monkeys. 9D5-positive microglia and blood vessels were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Consistent with such a mechanism, they observed that treatment with 3D6 led to increased microglial colocalization with amyloid deposits in vivo. We have also observed that pyroGlu-3 peptides can be observed in microglia in the APP/PS1KI mouse model as an indication of phagocytotic activity [109]. …”
Section: N-truncated Aβ As a Target For Immunotherapymentioning
confidence: 99%
“…Consistent with such a mechanism, they observed that treatment with 3D6 led to increased microglial colocalization with amyloid deposits in vivo. We have also observed that pyroGlu-3 peptides can be observed in microglia in the APP/PS1KI mouse model as an indication of phagocytotic activity [109]. …”
Section: N-truncated Aβ As a Target For Immunotherapymentioning
confidence: 99%
“…A 500 mg dose of the antibody resulted in improvement in acquisition learning in the water T-maze test in A␤PPswe/PS1dE9 transgenic mice. Note that oligomeric pyroglutamate A␤ is present in microglia and a subfraction of vessels in patients with AD, which has implications for immunotherapy [665] (Thomson Reuters Pharma, update of December 23, 2013).…”
Section: Antibodies Against Amyloid-βmentioning
confidence: 99%
“…It has been shown that the main component of senile plaques from AD patients is pE –Aβs, especially pE−Aβ 3‐40/42. In addition, some studies suggested that pGlu‐Aβ is critical to the development of AD, especially in the early stage . Therefore, QC represents an attractive target to develop novel treatments for AD .…”
Section: Introductionmentioning
confidence: 99%